2014
DOI: 10.1007/s13142-014-0275-y
|View full text |Cite
|
Sign up to set email alerts
|

Bridging the gap between research and practice: an assessment of external validity of community-based physical activity programs in Bogotá, Colombia, and Recife, Brazil

Abstract: For more than a decade, physical activity classes have been offered in public places at no cost to the participants in some Latin American cities, however, internal and external validity evidence of these programs is limited. The goals of this study were to assess, report, and compare the external validity of the Recreovia program (RCP) in Colombia, and the Academia da Cidade program (ACP) in Brazil. Interviews to assess external validity of the RCP and ACP were conducted in 2012. The interview guide was devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
57
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(63 citation statements)
references
References 37 publications
(50 reference statements)
1
57
0
3
Order By: Relevance
“…Two recent articles have outlined hurdles facing the mHealth community 50, 79 . The fact that the field changes so quickly is one of the major challenges.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two recent articles have outlined hurdles facing the mHealth community 50, 79 . The fact that the field changes so quickly is one of the major challenges.…”
Section: Resultsmentioning
confidence: 99%
“…Ubiquitous mHealth technologies are also providing unprecedented opportunities to understand behavior in place, time and context through ongoing access to temporally dense, highly contextualized data 50 . Interactive technologies for real-time, contextualized obesity monitoring and interventions provide a level of ecological validity only attainable through observation and intervention ‘in the wild’ 51 .…”
Section: Fast-paced Development Of Mobile Technologies For Obesity Prmentioning
confidence: 99%
“…High-resolution communications about behaviors can thus help fundamentally advance behavioral theories by improving our understanding of the mechanisms behind behavior changes and choices that happen every day. The behavioral science community has identified that more real-time data sources are needed to better understand how and why people make decisions especially related to health [64, 80]. High-resolution behavior communications can could potentially be linked to appropriate representations of off-line behavior (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…The participants included a current coordinator (2011-2016) and coordinators from three previous terms (1999-2004, 2005-2006, 2007-2010). The survey included questions on the structure of the program, users, instructors, physical activity sessions and budget and responses were recorded and transcribed 6 . Subsequently, five categories were created for coding: 1) resources, 2) activities, 3) outcomes, 4) short-term results and 5) long-term results 7 .…”
Section: Construction Of the Logic Modelmentioning
confidence: 99%
“…The Recreovía Program, created in Bogota (Colombia) in 1995, consists in sessions of physical activity, coordinated and musicalized, in plazas, parks, commercial centers and jails 2,5 . This program promotes activities for the community 3,6 and participation has been associated with higher physical activity levels, especially in women 5 . The aim of this study was to develop a logic model of the Recreovía Program in Bogota, Colombia.…”
Section: Introductionmentioning
confidence: 99%